INTERPRETATION OF OPEN LEGAL POLICY BY THE CONSTITUTIONAL JUDGES IN JUDICIAL REVIEW OF PARLIAMENTARY THRESHOLDS - Sholahuddin Al-Fatih (Diponegoro Law Review, 2021)
This study attempted to discuss the interpretation of open legal policy by constitutional judges in terms of reviewing legislation related to the legal norms of parliamentary thresholds. Through conceptual and statutory approaches, this study tries to examine the ways or models of interpretation conducted by constitutional judges. This research uses Aharon Barak's thinking on the concept of legal interpretation a benchmark and an analytical tool. The results of this study show that the interpretation conducted by the constitutional judge relating to a norm that is considered an open legal policy is appropriate. This research is expected to help academics and legal practitioners, especially with regard to election law to be able to dig deeper into models of legal interpretation, not only based on the idea of Aharon Barak but also by other thinkers or experts.